The effects of carica papaya linn. latex on the healing of burn wounds in rats - Ahmad Nazrun Shuid,; Mohd Syukri Anwar,; Ahmad Asmadi Yusof, (penerbit ukm, 2005)
This study was carried out to compare the rate of burn wound healing with the applications of the latex of Carica papaya Linn. (papaya) or of silver sulfadiazine cream (SSD). Partial and full thickness burn wound (2 cm x 2 cm) was induced on the dorsal part of anaesthetized rats by using heated metal plates. The rats were divided into three groups, i.e. untreated group and groups treated daily with SSD and papaya latex, respectively. A digital camera was used to take photographs of the burn wounds daily to monitor their healing. It was found that there was no significant difference in the healing time of papaya latex treated group compared to the SSD treated group. Papaya latex contained digestive enzymes which might clean burn wounds but might also cause wound bleeding in a few rats of the papaya latex group.